2015
DOI: 10.1556/0806.43.2015.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of aflatoxin B1 molecules on gold SPR chip surface using functionalized gold nanoparticles

Abstract: Due to the warm and favourably humid climate of Southern Hungary, the maize is one of the most important crops. The protection against crop damage caused by fusarium and Aspergillus species is essential. Detection of aflatoxin B1 (AFB1) molecules in cereal crops by selective sensors is important, while they can cause serious diseases in humans and animals if they enter the food chain. Our main objective was to develop selective AFB1 sensor with increased sensitivity applying βCD-functionalized gold nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It has been reported that by increasing the concentration of analyte on the SPRi sensor chip surface, signals in term of response unit increases due to the binding of antigen and antibody (Park et al, 2014). Similarly, Majzik et al, also studied the interaction of AFB 1 to anti-AFB 1 biomolecules (Majzik et al, 2015). It has also been exposed that by increasing the AFB 1 concentration into the flow system, AFB 1 analyte bind with immobilized molecules over the sensor surface results to change in SPRi signal.…”
Section: Spri-based Afb 1 Detectionmentioning
confidence: 99%
“…It has been reported that by increasing the concentration of analyte on the SPRi sensor chip surface, signals in term of response unit increases due to the binding of antigen and antibody (Park et al, 2014). Similarly, Majzik et al, also studied the interaction of AFB 1 to anti-AFB 1 biomolecules (Majzik et al, 2015). It has also been exposed that by increasing the AFB 1 concentration into the flow system, AFB 1 analyte bind with immobilized molecules over the sensor surface results to change in SPRi signal.…”
Section: Spri-based Afb 1 Detectionmentioning
confidence: 99%
“…Its disadvantage is that although it is sensitive, it is not selective in the case of complex samples. However, the required selectivity can be achieved by prior sample clean-up with immunoaffinity column, providing a clean solution without interferences ( Majzik et al, 2015 ).…”
Section: Separation Techniquesmentioning
confidence: 99%
“…Majzik et al demonstrated the sensitive detection method for AFB 1 molecules onto the gold SPR disk using the functionalized AuNPs (Majzik et al 2015). The thiolmodified cyclodextrin and gold b-cyclodextrin functionalized AuNPs immobilized onto the surface through covalent bonding.…”
Section: -D Optical Biosensormentioning
confidence: 99%